If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(6x) = 9 Remove parenthesis around (6x) ln * 6x = 9 Reorder the terms for easier multiplication: 6ln * x = 9 Multiply ln * x 6lnx = 9 Solving 6lnx = 9 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '6nx'. l = 1.5n-1x-1 Simplifying l = 1.5n-1x-1
| 1x-7=3x-5 | | -6z+3=-9-9(z-12) | | -x/3=5=21 | | 1300=p+p(.01) | | 18=2/5x-6 | | -4x^2-28x=0 | | log^7(117649)=x | | x/3-14=-8 | | lnx+ln(x+15)=2 | | 9n+1=99 | | p^2+3p= | | 12lnx=24 | | 6c-12=-2+9(c+2) | | (2x^2/3y^-5)^3 | | 2783.8x=1892.5 | | ln(x)+ln(x+15)=2 | | 3586.7x=2892.5 | | 55x=175 | | 12x^2+22x-18=0 | | 1x=56 | | (4x/7y^3)^2 | | 2x-4=20+2x | | -4x+7y-3z=-10 | | 2x-8=20-6x | | Y-x= | | 2log(x+9)-2=0 | | 9x-36+63=180 | | 2x-8=20-14x | | 4K+7=35+1.2k | | 2x+9x^2=c^2 | | 5x+10y=625 | | 2(4x-3)=4(2x+8) |